Evaluating software tools to conduct systematic reviews: a feature analysis and user survey - Marta Pellegrini; Francesco Marsili (Firenze University Press, 2021)
Systematic reviews are research synthesis methods increasingly used in educational research to support evidence-based decision making. The conduction of a systematic review is a complex process with several phases usually supported by software tools. These tools used at the international level are not currently common in the Italian educational research. This work describes four software tools used in the international educational research and evaluates their general functionality and specific features' usability to conduct the systematic review phases of study screening and selection. For this purpose, this study uses two methods: a feature analysis (Kitchenham et al., 1997) and an expert survey (Harrison et al., 2020). The results of both investigation methods agree to consider Covidence and Rayyan the most functional software tools in conducting SR. Among the four tools, ASReview has the greatest potential for making the process of a SR more efficient.   Una valutazione dei software per condurre revisioni sistematiche: analisi delle caratteristiche e sondaggio a esperti Le revisioni sistematiche sono metodi di sintesi di ricerca sempre più utilizzati in campo educativo al fine di supportare il processo decisionale basato su evidenze. La conduzione di una revisione sistematica, poiché complessa e su più fasi, è sovente supportata in ambito internazionale da software specifici attualmente poco diffusi nella ricerca educativa italiana. Il contributo presenta quattro software utilizzati nella ricerca educativa internazionale e valuta le funzionalità generali e l'usabilità di caratteristiche specifiche per condurre le fasi di screening e di selezione degli studi. A questo scopo lo studio impiega i metodi dell'analisi delle caratteristiche (Kitchenham et al., 1997) e del sondaggio ad esperti in revisioni sistematiche (Harrison et al., 2020) in campo educativo. I risultati di entrambi i metodi di indagine concordano nel ritenere Covidence e Rayyan gli strumenti più funzionali per condurre revisioni sistematiche, mentre ASReview risulta il software con maggiore potenzialità per rendere il processo più efficiente.